Optimization of Job Shop Scheduling Using a Hybrid Active Non-Delay Scheduling Algorithm at PT Propan Raya - Wirawan, Bryan Eka; Sutrisno, Sutrisno (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Inefficient production scheduling is still a major challenge in job shop manufacturing systems, especially in industries with high complexity such as PT Propan Raya. Inaccuracies in resource allocation and work order often lead to long turnaround times, low machine utilization, and failure to achieve production targets. This research responds to these challenges by proposing the application of the Hybrid Active-Non Delay Schedule algorithm, which combines the principles of prioritization of critical operations and utilization of work time without delay. With this approach, scheduling is designed not only to avoid idle time, but also optimize the overall production flow. This study shows that the application of the algorithm is able to construct a work order that is more adaptive to the real conditions in the field, resulting in a significant increase in efficiency and productivity. These results demonstrate that the integration of algorithmic approaches in production scheduling can be a strategic solution for industries seeking to improve competitiveness and operational sustainability.